Luminescence properties of Ge and Ge-Si structures on silicon-based microcavities - Xiaoyu Zhou; Ziyang Zhou; Wenqian Wu; Weiye Yang; Hongyan Peng; Shihua Zhao (PLoS ONE, 2025)
Utilizing laser etching technology under specific laser parameters (laser energy 250 mJ, repetition rate 1 Hz, pulse width 30 ns, spot diameter 150 µm), single-crystal silicon was etched, followed by the deposition of materials onto silicon-based microcavity samples using the pulsed laser deposition method. The Ge-coated microcavity samples were characterized using SEM and EDS, revealing cluster formations at the edges of the microcavities with the presence of germanium within these clusters. Photoluminescence spectroscopy identified characteristic luminescence peaks due to transverse optical (TO) phonon vibrations at 695 nm in the Ge-coated microcavity samples. Subsequently, the Ge-coated microcavity samples were subjected to high-temperature annealing at 1000 °C. After annealing for 30 min, a sharp luminescence peak at 700 nm associated with Ge-O bonds was observed. Finally, a layer of Si was deposited over the Ge-coated samples using pulsed laser deposition, resulting in a Ge-Si bilayer structure. After annealing at 1000 °C, this bilayer structure exhibited two distinctive peaks at 700 nm and 940 nm, with the former being a sharp peak due to Ge-O bonds and the latter due to the formation of Si-Si bonds within the clusters.